Relationship Between Academic Stress and Learning Achievement in Nursing Student - Panma, Yuanita (CV. Inara, 2021)
The stress experienced by most students is academic stress. This academic stress is closely related to students' academic processes and the environment that affects the academic process. The purpose of this study was to determine the relationship between academic stress and student learning achievement. This study was a cross-sectional design with purposive sampling of 126 respondents. Data were collected at a nursing academy in Jakarta in 2018. The instrument used was the Student Life Stress Inventory (SLSI) questionnaire. Results showed most students were female(88.9%), from Senior High School majoring in science (38.9%), very satisfyinglearning achievement (91.3%), and experience severe academic stress (55.6%). There is no significant relationship between learning achievement and academic stress (p = 0.317) and gender (p-value 0.370). There is a significant relationship between learning achievement and sebior high school majoring (p=value 0.005) and age (p-value 0.007). Institutions should identify sources of the academic stressor and apply appropriate coping mechanisms to reduce academic stress.Keywords:academic stress, learning achievement, nursing student.